Agricultural Implications of the Fukushima Nuclear Accident 2016
DOI: 10.1007/978-4-431-55828-6_4
|View full text |Cite
|
Sign up to set email alerts
|

Cesium Accumulation in Paddy Field Rice Grown in Fukushima from 2011 to 2013: Cultivars and Fertilization

Abstract: After the accident at the Fukushima Daiichi Nuclear Power Plant, radioactive cesium (Cs) was released and the agricultural fields in Fukushima were contaminated. It became important to obtain data for radioactive Cs accumulation in rice grown in contaminated fields. We conducted a 3-year investigation in a Fukushima paddy field of radioactive Cs concentrations in various rice cultivars, and in two commercial rice cultivars grown under four different nutrient conditions. Our studies demonstrated substantial var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Agricultural crop selection was also investigated in Japan as a countermeasure for reducing Cs uptake in the food chain. Ohmori et al (2013) reported a 10-fold difference in Cs uptake for 58 rice cultivators. A similar reduction was obtained growing oriza bean (Win et al 2016).…”
Section: Plant-based Countermeasuresmentioning
confidence: 99%
“…Agricultural crop selection was also investigated in Japan as a countermeasure for reducing Cs uptake in the food chain. Ohmori et al (2013) reported a 10-fold difference in Cs uptake for 58 rice cultivators. A similar reduction was obtained growing oriza bean (Win et al 2016).…”
Section: Plant-based Countermeasuresmentioning
confidence: 99%
“…Deficiency of K leads to enhanced Cs accumulation in rice plants (Nobori et al., 2016; Ohmori et al . 2016). Uptake of Cs in K‐deficient environments is mediated primarily by the high affinity K transporter, OsHAK1 (Nieves‐Cordones et al., 2017; Rai et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, field studies in Cs‐contaminated rice paddies showed that increased N fertilization enhanced Cs uptake under reduced K fertilization conditions (Ohmori et al . 2016). This may be due to increased Cs availability in the rhizosphere, as Cs in the soil can be exchanged with ammonium ions (Ohmori et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation